2020
DOI: 10.1111/jam.14778
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of dermatophytes based on currently available methods – a comparative study

Abstract: Aims: Accurate identification of dermatophytes is essential for implementing appropriate antifungal treatment and epidemiological analysis. However, the limitations of conventional diagnostics are a frequently discussed topic, and new diagnostic techniques are constantly expanding. In this study, we assess the suitability of conventional diagnostic techniques in comparison to the realtime PCR assay and MALDI-TOF MS in detection and identification of dermatophytes. Methods and Results: Strains included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 49 publications
0
30
1
3
Order By: Relevance
“…Moreover, the agreement of the positive qPCR result with the dermatophyte culture was 10.98% (50% vs. 39.02%) higher for this method than for the microscopic examination. Gnat et al [23] revealed that the qPCR method with pan-dermatophyte primers detected dermatophytes in a sample with a 24.5% (85.4% vs. 60.9%) and 53.7% (85.4% vs. 31.7%) higher efficiency than direct analysis in fluorescence and light microscopy, respectively. This result was therefore much better than that obtained in the present research, the reasons for which can be found in the greater diversity of the analyzed samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the agreement of the positive qPCR result with the dermatophyte culture was 10.98% (50% vs. 39.02%) higher for this method than for the microscopic examination. Gnat et al [23] revealed that the qPCR method with pan-dermatophyte primers detected dermatophytes in a sample with a 24.5% (85.4% vs. 60.9%) and 53.7% (85.4% vs. 31.7%) higher efficiency than direct analysis in fluorescence and light microscopy, respectively. This result was therefore much better than that obtained in the present research, the reasons for which can be found in the greater diversity of the analyzed samples.…”
Section: Discussionmentioning
confidence: 99%
“…Mycological procedures, i.e., detection and species identification of the isolates, were performed with a few modifications, as described previously by Gnat et al [23]. For the qPCR technique (P), DNA was extracted using a DNeasy Blood & Tissue Kit (Qiagen, Hilden, Germany), according to the manufacturer's instructions.…”
Section: Laboratory Diagnostics Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some patients had macroscopically conspicuous lesions, no dermatophyte was detected by extensive mycological diagnostics. Detection of fungi involved in superficial skin infections by conventional methods still is the gold standard though it is very time‐consuming and not always successful 20 . The limitations of conventional diagnostics are therefore a frequently discussed topic, as new diagnostic techniques are constantly expanding.…”
Section: Discussionmentioning
confidence: 99%
“…W niektórych przypadkach dokładna identyfikacja na poziomie gatunku nie jest możliwa wyłącznie w oparciu o sekwencjonowanie regionów ITS [38,39,46]. Obecnie jednak nie są znane alternatywne markery molekularne, dla których uzyskuje się porównywalną zdolność rozdzielczą.…”
Section: Wyzwania Bioinformatyczneunclassified